Surface-oxidised carbon nanofibre-based nanofluids: Structural, morphological, stability and thermal properties - Abdullah, Norli; Norizan, Mohd Nurazzi; Janudin, Nurjahirah; Mohd Kasim, Noor Azilah; Mohd Saidi, Norshafiqah; Osman, Mohd Junaedy; Mohamad, Imran Syakir; Mohd Rosli, Mohd Afzanizam (MDPI, 2022)
The reputation of nanofluids as a convenient heat transfer media has grown in recent years. The synthesis of nanofluids is often challenging, particularly carbon-based nanofluids, due to the rapid agglomeration of the nanoparticles and the instability of the nanofluids. In this regard, surface modification and surfactant addition are potential approaches to improve the physical and thermal properties of carbon-based nanofluids that have been studied and the structural, morpho-logical, and thermal characteristics of surface-oxidised carbon nanofibre (CNF)-based nanofluids has been characterised. Commercial CNF was first subjected to three different acid treatments to introduce surface oxygen functional groups on the CNF surface. Following the physical and thermal characterisation of the three surface-oxidised CNFs (CNF-MA, CNF-MB, and CNF-MC), including Raman spectroscopy, Fourier transform infrared (FTIR), thermogravimetric analysis (TGA), and field emission scanning electron microscopy (FESEM), the CNF-MB was selected as the best method to synthesise the surface-oxidised CNF-based nanofluid. A total of 40 mL of ultrapure water was used as a pure base fluid and mixed with the surface-oxidised CNF at a concentration range of 0.1– 1.0 wt.%, with a fixed of 10 wt.% amount of polyvinylpyrrolidone (PVP). The thermal conductivity of CNF-based nanofluid was then characterised at different temperatures (6, 25, and 40 °C). Based on the results, surface oxidation via Method B significantly affected the extent of surface defects and effectively enhanced the group functionality on the CNF surface. Aside from the partially defective and rough surface of CNF-MB surfaces from the FESEM analysis, the presence of surface oxygen functional groups on the CNF wall was confirmed via the Raman analysis, TGA curve, and FTIR analysis. The visual sedimentation observation also showed that the surface-oxidised CNF particles remained dispersed in the nanofluid due to the weakened van der Waals interaction. The dispersion of CNF particles was improved by the presence of PVP, which further stabilised the CNF-based nanofluids. Ultimately, the thermal conductivity of the surface-oxidised CNF-based nanofluid with PVP was significantly improved with the highest enhancement percentage of 18.50, 16.84, and 19.83% at 6, 25, and 40 °C, respectively, at an optimum CNF concentration of 0.7 wt.%.